2009
DOI: 10.4049/jimmunol.0901615
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Waves Initiate Antigen-Stimulated Ca2+ Responses in Mast Cells

Abstract: Ca2+ mobilization is central to many cellular processes, including stimulated exocytosis and cytokine production in mast cells. Using single cell stimulation by IgE-specific Ag and high-speed imaging of conventional or genetically encoded Ca2+ sensors in rat basophilic leukemia and bone marrow-derived rat mast cells, we observe Ca2+ waves that originate most frequently from the tips of extended cell protrusions, as well as Ca2+ oscillations throughout the cell that usually follow the initiating Ca2+ wave. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 76 publications
(83 reference statements)
6
51
0
1
Order By: Relevance
“…Our previous studies demonstrated that Ca 2+ responses to antigen in RBL mast cells usually initiate as waves that begin at the tips of extended cell protrusions (Cohen et al, 2009), and these results prompted us to investigate whether degranulation is influenced by Ca 2+ waves. To monitor Ca 2+ mobilization and degranulation simultaneously in the same cells, we used Fura Red as the Ca 2+ indicator in cells that were preloaded with FITC-dextran.…”
Section: Simultaneous Imaging Of Ca 2+ and Degranulation Responsesmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies demonstrated that Ca 2+ responses to antigen in RBL mast cells usually initiate as waves that begin at the tips of extended cell protrusions (Cohen et al, 2009), and these results prompted us to investigate whether degranulation is influenced by Ca 2+ waves. To monitor Ca 2+ mobilization and degranulation simultaneously in the same cells, we used Fura Red as the Ca 2+ indicator in cells that were preloaded with FITC-dextran.…”
Section: Simultaneous Imaging Of Ca 2+ and Degranulation Responsesmentioning
confidence: 99%
“…7A, left side, only a small percentage of exocytotic events occurred along protrusions compared with the cell body at this high antigen dose, and the difference in total number of events for cells that initiate Ca 2+ responses as P-waves versus Bwaves was small. These cells were shown to initiate Ca 2+ waves from protrusions with a higher probability at low doses of antigen (Cohen et al, 2009), and we investigated whether a low dose of antigen (1.7 ng/ml) caused a higher probability of exocytosis along these extended protrusions than seen with a high dose of antigen. When this low dose of antigen was used to stimulate degranulation, the average number of exocytotic events per cell was less than at the high antigen dose, and this difference was particularly evident for cells with Ca 2+ waves that initiated in the cell body (Fig.…”
Section: Simultaneous Imaging Of Ca 2+ and Degranulation Responsesmentioning
confidence: 99%
See 3 more Smart Citations